Produtividade e valor nutritivo de pastagens de capim elefante sob os sistemas orgânico e convencional - Bem, Cláudia Marques de (2014)
The objective of this research was to evaluate the productivity and nutritive value of elephant grass pastures, subjected to conventional and organic production system. In the conventional system elephant grass was planted in rows 1.2 m apart from each other. In the organic system elephant grass was planted in rows 3 m apart from each other. In the space between rows, in cool season, annual ryegrass was sown; allowing the development of spontaneous growing species in the warm season. It was applied 100 kg of N/ha from chemical and organic fertilizers (manure of cattle and pig slurry) in the respective pastures. The grazing method was rotated with time to occupy the two days. Holstein cows receiving 0.9% of body weight complementary concentrate feed were used. Pre and post grazing forage mass, botanical and structural composition, forage production and stocking rate were evaluated. Hand-plucked samples were collected to analyze chemical composition and digestibility. Experimental design was completely randomized with two treatments (forage systems), three replicates (paddocks) and repeated measures (mean values of grazing cycles or season). Eight and seven grazing cycles were performed during the experimental period for respective systems. Organic system present best forage distribution thought the year and highest participation of elephant grass leaf blades on herbage mass. The pasture under conventional system presented higher forage mass and stocking rate. Similar value was found in the chemical composition and digestibility of elephant grass pastures in both pasture systems. The organic as much as conventional system showed high qualitative values considering the fertilization, manage and utilization time, in proposed strategy. The results show that the elephant grass can be used under the organic system proposed.